The Effect of the Continuity of the ISMUBA In Action Program on the Religious Literacy Ability of Students at MA Muhammadiyah 1 Weleri - Raudina Amalia Romantika; Sutipyo Ru'iya (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
This study aims to analyze how much the continuity of the ISMUBA in action program affects the religious literacy skills of students at MA Muhammadiyah 1 Weleri. This study uses an associative quantitative method. The data was obtained through a questionnaire filled out by 85 students at MA Muhammadiyah 1 Weleri. The sample determination technique uses the Non-Prability Sampling method. The data analysis techniques used are descriptive and inferential statistics through simple linear regression analysis to test the influence between independent and dependent variables. The results of this study show that the ISMUBA in action program has a positive impact on the religious literacy ability of students at MA Muhammadiyah 1 Weleri. The ISMUBA in action program can also be a good predictor of the rise and fall of the religious literacy skills of students at MA Muhammadiyah 1 Weleri. This research has the implication that the ISMUBA in action program and other religious programs can be an alternative to improve students' religious literacy skills.